The Role of Volunteer for the Management of Conservation-based Ecotourism in Clungup Mangrove Conservation Tambakrejo Village, Sumbermanjing Wetan Sub-District, Malang - Ferik Antyo Agus Wibowo; Harsuko Riniwati; Iwan Nugroho (Journal of Indonesian Tourism and Development Studies, 2018)
Clungup Mangrove Conservation (CMC) is the coastal area with the most complete ecosystem in Malang District. Since 2014, this place started to be known as the area of the conservation (tourism-based) with the best management, so it won the 1st Adhibakti Minabahari with the category of Coastal Postponed Development. This achievement strongly supported by the role of volunteers who fight for the ecotourism management. Volunteer role is included the community involvement in the conservation activities in the region, starting from the CMC continues on the institutional establishment of ecotourism manager for CMC. The objectives of the study are to know and analyze the role of a volunteer on the management and the sustainability of the CMC ecotourism. The methods that were used are field observation, interview with the key stakeholders, and multi-dimension scale (MDS) method to analyze the sustainable management of CMC. The results of the survey revealed very important volunteer roles that involve 6 volunteer’s efforts from the beginning to the creation of ecotourism management by initiating rehabilitation, the establishment of institutional, and create jobs. Increasing the quality of ecology is indicated with an increase in mangrove covering through rehabilitation projects, an increase in coral reefs covering and abundance coral fishes, and economic benefits of additional income for 108 local people who work in ecotourism sector in CMC area. The average value of volunteer’s sustainability role in ecotourism management of CMC obtained with the acquisition of four-dimensional index value of 71.45. This value showed that aspects of ecology, social, economic, and institutional in ecotourism of CMC is fairly supported the sustainable development of ecotourism-based conservation in CMC.Keywords: Clungup Mangrove Conservation, ecotourism, sustainable, volunteer.